Evaluating the respective weights of some facial signs on the perceived radiance/glow in differently aged women of six countries. Issue 6 (1st July 2021) - Flament, Frederic; Ye, Chengda; Mercurio, Daiane Garcia; Abric, Aurelie; Sewraj, Poonam; Velleman, Damien; Yamamoto, Sawako; Prunel, Anne; Colomb, Loic
Abstract: Objectives: To evaluate the impact of Facial radiance or Glow on the perception of age (PA) and to assess which facial signs most influence PA. Material and Methods: The faces of 1058 differently aged women (18‐80 years) of six different ethnicities/countries (China, Japan, Korea, India, South Africa, and Brazil) were photographed under standard conditions. These allowed to focus on 20 different facial signs that were further graded by experts, using referential Atlases dedicated to facial aging. In each of the six countries, 100 local women were recruited as naïve panels to express their perceptions on Glow and Age on each full‐face photograph (blind coded) of the local studied woman. Results: A decreased Glow/Radiance appears clearly associated with an increased perceived age in all studied subjects, especially among Chinese, Japanese, and South African women. With regard facial signs, Skin texture (Wrinkles of all kinds), Ptosis/Sagging, and Pigmentation signs prevail in almost all women at the exception of South African women where Pigmentation signs and Cheek skin pores largely predominate in the perception of both Glow and PA. Pigmentation signs are of a very high weight among Chinese and Japanese women. Conclusion: Despite some collective agreements, the present study shows some specificities within the women of the six ethnicities/countries. PA, a core index of antiaging strategies, goes along with facial Glow in almost all studied women. The duller the facial skin, the older it is perceived.